Impact of Status and Meme Content on the Spread of Memes in Virtual Communities - Mazambani, Gideon; Carlson, Maria; Reysen, Stephen; Hempelmann, Christian (Human Technology, 2015)
We examined the influence of meme consistency (vs. inconsistency) and intragroup status on the spread of memes in virtual communities. Prior research suggests that information consistent with the theme of the group is remembered better and that ideas threatening to the group identity are rejected. In addition, previous research shows that low-status group members mimic high-status members and communicate with them to seek information and approval. We analyzed social interactions among members of four online forums from January 1, 2010, to February 21, 2014. Contrary to our prediction, our results show that memes initiated by low-status members spread faster than memes started by high- or moderate-status members. In line with prior research, memes that were consistent with a forum theme were spread more frequently than inconsistent memes.